Internal Corporate Governance Mechanisms and Corporate Tax Avoidance in Nigeria: A Quantile Regression Approach - Egbunike, Francis Chinedu; Gunardi, Ardi; Ugochukwu, Udunze; Hermawan, Atang (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021)DO - 10.24843/JIAB.2021.v16.i01.p02, 2021)
The main objective of the study was to investigate the effect of corporate governance on tax avoidance of quoted manufacturing firms in Nigeria. The study focused on internal corporate governance mechanisms and specifically examined the effect of board size, board independence, board diligence, CEO duality, and audit committee diligence. The ex post facto research design was adopted. The population comprised of all quoted manufacturing companies on the Nigerian Stock Exchange (NSE). The sample was purposively drawn as all companies in the consumer goods sector of the NSE. The study relied on secondary data obtained from annual reports and accounts of the sampled companies. Both descriptive and inferential statistics were used to analyze the data. The hypotheses were validated using Quantile Regression technique. Results showed that board size, board independence, and board diligence were significant at the median and 75th quantile. CEO duality and audit committee diligence were not significant at the 25th, 50th, and 75th quantile. The study recommended among others moderate board sizes to improve efficiency of decision-making. In addition, the need for more independent directors and meeting frequency should be tailored to suit the needs of the company. Keywords : corporate governance mechanisms, tax avoidance, quantile regression